PENGARUH PRESTASI KERJA, LOYALITAS KERJA TERHADAP PROMOSI JABATAN DI PT. BALI PAWIWAHAN COCO GROUP - Sungkono, Sandra Wijayanti; Dewi, IGA Manuati (E-Jurnal Manajemen, 2017)
This study aims to examine the effect of job performance and loyalty towards promotion work in PT. Bali Pawiwahan Coco Group Retail Division, Jimbaran Badung. Samples used were as 86 people were determined with saturated sampling. Data collection techniques used questionnaires and were analyzed data by using multiple linear regression. The results of the analysis of performance show significant positive effect on promotion at PT. Bali Pawiwahan Coco Group Retail Division, Jimbaran Badung. Moreover, loyalty significant positive effect on employment promotion at PT. Bali Pawiwahan Coco Group Retail Division, Jimbaran Badung .
Keywords: job performance; loyalty; promotions